Enhancing glucose metabolism via gluconeogenesis is therapeutic in a zebrafish model of Dravet syndrome. Issue 1 (25th January 2021) - Banerji, Rajeswari; Huynh, Christopher; Figueroa, Francisco; Dinday, Matthew T; Baraban, Scott C; Patel, Manisha
Abstract: Energy-producing pathways are novel therapeutic targets for the treatment of neurodevelopmental disorders. Here, we focussed on correcting metabolic defects in a catastrophic paediatric epilepsy, Dravet syndrome which is caused by mutations in sodium channel NaV1.1 gene, SCN1A . We utilized a translatable zebrafish model of Dravet syndrome ( scn1lab ) which exhibits key characteristics of patients with Dravet syndrome and shows metabolic deficits accompanied by down-regulation of gluconeogenesis genes, pck1 and pck2 . Using a metabolism-based small library screen, we identified compounds that increased gluconeogenesis via up-regulation of pck1 gene expression in scn1lab larvae. Treatment with PK11195, a pck1 activator and a translocator protein ligand, normalized dys-regulated glucose levels, metabolic deficits, translocator protein expression and significantly decreased electrographic seizures in mutant larvae. Inhibition of pck1 in wild-type larvae mimicked metabolic and behaviour defects observed in scn1lab mutants. Together, this suggests that correcting dys-regulated metabolic pathways can be therapeutic in neurodevelopmental disorders such as Dravet syndrome arising from ion channel dysfunction. Abstract : Banerji et al. identified a gluconeogenesis modulator, PK11195, a known mitochondrial translocator protein ligand that normalized metabolic deficits and suppressed electrographic seizures in a pre-clinical zebrafish model of Dravet syndrome. This suggests a novel metabolism-based therapeutic avenue to treat catastrophic paediatric epilepsies such as Dravet syndrome arising from ion channel mutations. Graphical Abstract: